Patient education program for Brazilians living with diabetes and prediabetes: findings from a development study - Gabriela Lima de Melo Ghisi; Mariana Balbi Seixas; Daniele Sirineu Pereira; Ligia Loiola Cisneros; Danielle Guedes Andrade Ezequiel; Crystal Aultman; Nicole Sandison; Paul Oh; Lilian Pinto da Silva (BMC, 2021)
Abstract Background Globally, the incidence of diabetes is increasing and strategies to reach a comprehensive approach of care are needed, including education in self-management. This is particularly true in low and middle-income countries where the number of people living with diabetes is higher than in the high-income ones. This article describes the development of a structured patient education program for Brazilians living with diabetes or prediabetes. Methods These steps were undertaken: 1) a 4-phase needs assessment (literature search of local diabetes guidelines, environmental scan, evaluation of information needs of patients identified by diabetes experts, and patient focus groups); and, 2) the translation and cultural adaptation of the patient guide (preparation, translation, back-translation, back-translation review, harmonization, and proofreading). Results Four of the seven guidelines identified include educational aspects of diabetes management. No structured education program was reported from the environmental scan. Regarding the information needs, 15 diabetes experts identified their patients' needs, who referred that they have high information needs for topics related to their health condition. Finally, results from six patient focus groups were clustered into six themes (self-management, physical activity, eating habits, diabetes medication, psychosocial being, and sleep), all embedded into the new education program. Constructive theory, adult learning principles, and the Health Action Process Approach model were used in program development and will be used in delivery. The developed program consists of 18 educational sessions strategically mapped and sequenced to support the program learning outcomes and a patient guide with 17 chapters organized into five sections, matched with weekly lectures. Conclusions This program is a sequential and theoretical strategic intervention that can reach programs in Brazil to support diabetes and prediabetes patient education.